Association between benign prostate hyperplasia and metabolic syndrome in men under 60 years old: a meta-analysis. Issue 11 (November 2019) - Wu, Shuiqing; He, Haiqing; Wang, Yinhuai; Xu, Ran; Zhu, Bin; Zhao, Xiaokun
Objective: To assess the potential relationship between benign prostate hyperplasia (BPH) and metabolic syndrome in men under 60 years old. Methods: We searched the Medline, Embase, and Web of Science databases for studies of patients with metabolic syndrome and BPH using the key words 'metabolic syndrome', 'benign prostatic hyperplasia', and 'BPH'. The odds ratios (ORs) and 95% confidence intervals (95%CIs) were extracted from the included studies and the role of metabolic syndrome in BPH and its characteristics (International Prostate Symptom Score (IPSS), total prostate volume (TPV), postvoid residual (PVR)) were evaluated by meta-analysis. Results: Six comparative studies comprising 61, 826 individuals were identified and included in this meta-analysis. There were significant correlations between metabolic syndrome and BPH (OR = 1.24, 95%CI = 1.19–1.29), clinical BPH (OR = 1.37, 95%CI = 1.03–1.70), and TPV (OR = 2.34, 95%CI = 1.25–3.42). However, there was no significant association between metabolic syndrome and IPSS (OR = 1.19, 95%CI = 0.35–2.04) or PVR (OR = 2.15, 95% CI = 0.95–3.34). Conclusions: These results indicate that metabolic syndrome is significantly and positively correlated with the incidence of BPH in younger men aged <60 years. However, there was no significant relationship between metabolic syndrome and BPH-related symptoms.